2020
DOI: 10.1080/15563650.2020.1817479
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of chloroquine and hydroxychloroquine following therapeutic use or overdose

Abstract: Introduction: While chloroquine, a derivative of quinine, has been used as an antimalarial for 70 years, hydroxychloroquine is now used to treat conditions such as rheumatoid arthritis and systemic lupus erythematosus. In 2020, hydroxychloroquine (and to a lesser extent chloroquine) also received attention as a possible treatment for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). During investigation for treating coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2, concerns for serious adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 153 publications
1
70
1
9
Order By: Relevance
“…Hydroxychloroquine (HCQ), an oral drug used for severe forms of rheumatoid arthritis and lupus erythematosus, has in vitro antiviral efficacy against coronaviruses including SARS-CoV-2 and immune modulating effects [ 3 , 4 , 5 , 6 , 7 ] and was among the first COVID-19 treatments investigated in human studies. HCQ, however, has several known adverse events such as QTc prolongation, cardiomyopathy, hypoglycemia and retinal toxicity in the non-COVID-19 environment [ 8 ]. By late Spring 2020, most of the evidence assessing HCQ efficacy and safety in hospitalized patients were from observational studies and showed widely divergent findings [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxychloroquine (HCQ), an oral drug used for severe forms of rheumatoid arthritis and lupus erythematosus, has in vitro antiviral efficacy against coronaviruses including SARS-CoV-2 and immune modulating effects [ 3 , 4 , 5 , 6 , 7 ] and was among the first COVID-19 treatments investigated in human studies. HCQ, however, has several known adverse events such as QTc prolongation, cardiomyopathy, hypoglycemia and retinal toxicity in the non-COVID-19 environment [ 8 ]. By late Spring 2020, most of the evidence assessing HCQ efficacy and safety in hospitalized patients were from observational studies and showed widely divergent findings [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works started to explore effects of HCQ on humans after it was proposed as an early treatment of COVID-19 patients ( Million et al, 2020 ). Several of them suggested short-term (days to weeks) toxicity at cardiac ( Doyno et al, 2020 ), cardiovascular ( Stevenson et al, 2020 ), and ocular ( Al Adel et al, 2020 ) tissues. According to Doyno et al (2020) , deaths from overdoses of HCQ most often result from cardiovascular collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Several of them suggested short-term (days to weeks) toxicity at cardiac ( Doyno et al, 2020 ), cardiovascular ( Stevenson et al, 2020 ), and ocular ( Al Adel et al, 2020 ) tissues. According to Doyno et al (2020) , deaths from overdoses of HCQ most often result from cardiovascular collapse. Several other effects have been reported by McChesney (1983) in association with the response of mammals after HCQ exposure.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 2361 patients who had used HCQ for more than 5 years found that when the cumulative dose exceeded 1000 g of HCQ, the risk of ocular toxicity significantly increased. [ 14 ] At a dose of 6.5 mg/kg, the risk of retinal toxicity within 5 and 10 years is less than 1% and 2%, respectively. [ 15 ] In addition, the deposition of HCQ in the cornea could decrease visual acuity.…”
Section: Discussionmentioning
confidence: 99%